The Influence of Auditor Professionalism and Auditor's Competency on Audit Quality - Widyanah Widyanah (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This research was carried out on Nasari Savings and Loans (KSP). The main objective of this research is to find out the influence of professionalism and auditor competence on audit quality on KSP Nasari. The method used in this research is descriptive method and verification method using a quantitative approach. The data used in this study is primary data. Data collection is done by direct observation, interviews, questionnaires and literature which is done by reading and studying books related to the problem. The population used for this study was 40 people, they consisted of Internal Control Unit (SPI) on KSP Nasari. The results of this study are professionalism and auditor competence positively and significantly affect audit quality.